Key directions of the Russian economy innovative development with the innovative activity practice of the integrated corporate structures - F. I. Shamhalov; R. V. Sizov (Статистика и экономика)
ARTICLE RETRACTEDThe article deals with the problems and the key directions of The article deals with the problems and key directions of innovative development of the Russian industry in connection with the need to reduce the dependence of the national economy on the situation on world commodity markets, as well as to create the conditions and incentives for the introduction and modern technologies development, improving energy and environmental efficiency of the economy and productivity for the development of economic sectors and industries, producing goods with high added value for the implementation of innovative projects and in general - to upgrade the socio-economic system of the country.The following statement is given: the development of innovative high-tech and knowledge-intensive industries must ensure import substitution products at the first stage, primarily in the militaryindustrial complex, and in the future - export-oriented competitive product.The article analyzes the experience of innovative activity of the integrated corporate structures with the participation of the state in the following areas: the integration of the industrial and financial capital; the concentration of capital (through the merger and acquisition of enterprises, strategic alliances); diversification of forms and fields of activity; globalization of activities (creation of subsidiaries in the most attractive countries and working on promising markets); capital internationalization (through the creation of transnational companies).On the basis of generalization of global corporate management experience in the state corporations the article analyzes key conditions and factors that determine the efficiency of the state-owned companies as a whole: a clear statement of goals and objectives of the state as the owner, whose interests go beyond the usual business purposes; fixing of these goals and objectives in the regulations, in the concepts and programs of long-term socioeconomic development of the country, in special agreements between the government and public sector enterprises, as well as in the statutes, in the policy and budgetary documents of state corporations; the creation of state corporations administration system that allows to carry out the separation of the control and management functions, to ensure coherence and consistency of the implementation of the asset management policy, the uniformity of the rules of management of state property on the basis of common rules; harmonization of interests of the state and private investors, their documentary fixation (for corporate plans, agreements between the parties, etc.) in order to limit undue state interference in the activities of state-owned companies, on the one hand, and protection from lobbying strain - on the other hand; increasing business transparency, which is the foundation of good governance; the establishment of effective operational management systems, including goal setting and planning, reporting, monitoring, control and evaluation of companies, risk management and information disclosure.